2020
DOI: 10.3390/brainsci10080490
|View full text |Cite
|
Sign up to set email alerts
|

Body Representations in Children with Cerebral Palsy

Abstract: We constantly process top-down and bottom-up inputs concerning our own body that interact to form body representations (BR). Even if some evidence showed BR deficits in children with cerebral palsy, a systematic study that evaluates different kinds of BR in these children, taking into account the possible presence of a general deficit affecting non-body mental representations, is currently lacking. Here we aimed at investigating BR (i.e., Body Semantics, Body Structural Representation and Body Schema) in child… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(35 citation statements)
references
References 29 publications
3
32
0
Order By: Relevance
“…Currently there is a lack of normative tests probing the different BRs. For this reason, BR tasks were carefully choose among experimental tasks that have proved to be very sensitive to detect BR deficit in several previous studies on adults with brain damage (Canzano, Piccardi, Bureca, & Guariglia, 2011;Guariglia & Antonucci, 1992;Schwoebel & Coslett, 2005) and children with cerebral palsy (Fontes et al, 2017;Di Vita et al, 2020). These tasks were also used in recent studies on the development of BRs in healthy children and young adults (Raimo et al, 2019) and on BR in older adults (Raimo et al, 2021).…”
Section: Body Representations Assessmentmentioning
confidence: 99%
“…Currently there is a lack of normative tests probing the different BRs. For this reason, BR tasks were carefully choose among experimental tasks that have proved to be very sensitive to detect BR deficit in several previous studies on adults with brain damage (Canzano, Piccardi, Bureca, & Guariglia, 2011;Guariglia & Antonucci, 1992;Schwoebel & Coslett, 2005) and children with cerebral palsy (Fontes et al, 2017;Di Vita et al, 2020). These tasks were also used in recent studies on the development of BRs in healthy children and young adults (Raimo et al, 2019) and on BR in older adults (Raimo et al, 2021).…”
Section: Body Representations Assessmentmentioning
confidence: 99%
“…To this aim, we conceived tasks similar to the ones used to test body representation, but which did not involve body-related stimuli (hereafter called control tasks). This set of tasks had been successfully used to test the development of body representations in healthy children and young adults (Raimo et al, 2019b), its impairment in cerebral palsy (Di Vita et al, 2019a) and its disruption after brain injury (Raimo et al, 2019a). As for the previous studies, all the tasks were performed on a laptop (13.3 ′′ display), equipped with a touch screen monitor.…”
Section: Body Representations Assessmentmentioning
confidence: 99%
“…Then, we divided them into two groups: 65 typically developing children from 7 to 8 years old (31 girls and 34 boys; 56 right-handed), and 37 typically developing children from 9 to 10 years old (24 girls and 13 boys; 30 right-handed). This group division was relevant since previous literature showed that children until 8 years of age do not reach optimal multisensory integration of visual and haptic information [ 35 , 36 ], do not reach an adult-like pattern regarding localizing body parts [ 16 ], and do not show significant differences in BR compared to children with atypical development [ 34 ].…”
Section: Methodsmentioning
confidence: 99%
“…According to the distinction of BR into action- and non-action-oriented [ 10 ], the assessment of BR was performed using a specific computerized battery previously used to assess BR in healthy children and adults [ 16 , 20 ], and in children and adults with brain damage [ 5 , 7 , 34 ]. The battery included BR tasks to evaluate both action (i.e., body schema) and non-action (i.e., body structural representation) oriented BR, and two corresponding control tasks, similar to those recording BR for features such as presentation and response modalities, but not including body stimuli and then not involving body processing.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation